Enjeux politiques de l’adaptation aux changements climatiques dans les projets de gestion intégrée des zones côtières à Madagascar - Jessica Onitsoa Andriamasinoro; Bruno Sarrasin (VertigO)
To cope with climate change, less developed country like Madagascar have been invited by the United Nations to submit a National Adaptation Programs of Action (NAPA) that identifies priority projects on climate adaptation. Integrated Coastal Zone Management (ICZM) is among these priority projects. This one is also due to an update of the Governmental policy on sustainable development of coastal and marine areas which have led to the development of a national strategy for sustainable development of coastal and marine areas in Madagascar. The analysis of PANA and ICZM however shows that they evolve in parallel and with few complementarities. From a political sociology perspective and based on documentary research and interviews conducted in Madagascar in 2013, this article will look first on how main stakeholder have “problematized” adaptation to climate change in Madagascar. Then, this will help us to better understand perceptions and tensions in defining problems and solutions associated with this theme, pointing out incompatibility of perceptions and actions in order to clarify the problems of implementation.